Transition Pandemic Towards Endemic? Local Government Preparedness in Surabaya City - Winoto, Suhartono (Jurnal Ilmiah Administrasi Publik, 2024)
The COVID-19 pandemic in June 2023 is declared to be over in Indonesia. Through Press No. 17 of 2023, President Joko Widodo declared the 2019 Corona Virus Disease (COVID-19) pandemic status over. To cope with an endemic era, governments need to adapt and formulate clear strategies. The local government has an important role to play in the transition from pandemic to endemic. The Regional Government, the Government of Surabaya City, has prepared a transition mechanism for endemics. The role of the actor and the coordination system have awakened well. The use of ICTs is also one of the instruments used in the endeavour of transitioning to endemic. The readiness of the government of Surabaya is a reflection of the government's readiness in the face of this transition. The aim of this study is to find out the readiness of the government of Surabaya to implement the pandemic-to-endemic transition from an adaptive governance perspective.  This research uses a soft system methodology to analyse data. The results of the study show that the government of Surabaya has implemented an adaptive system of government in which the mayor of Surabaya is the chief commander. Coordination and collaboration between actors are supported by ICT. The distribution of roles between planners and executives is clearly depicted.